Comparing the risk of cardiovascular disease between degarelix and gonadotropin-releasing hormone agonists:a systematic review and meta-analysis - Liu, Wencong; Liu, Zhenyu; Song, Liangdong; Zhu, Huixuan; Luo, Yu; Zhang, Jindong; Su, Shuai; Wang, Delin (Frontiers in Oncology, 2025)
BackgroundRegarding the comparison of cardiovascular disease risk between gonadotropin-releasing hormone (GnRH) antagonists and GnRH agonists, there are discrepancies in results from different studies. Therefore, this meta-analysis was conducted to investigate whether degarelix could reduce cardiovascular disease risk.MethodsWe systematically searched the PubMed, Embase, Web of Science, and Cochrane Library databases with a search time limit of up to December 2023 for articles focusing on the use of degarelix, a GnRH antagonist, in prostate cancer, with an emphasis on articles comparing degarelix to GnRH agonists. Study endpoints included major adverse cardiovascular events, stroke, all-cause mortality, myocardial infarction, heart failure, and arrhythmia.ResultsA total of 1320 articles were retrieved, of which eight met our inclusion criteria and involved 138–065 patients. The pooled results showed no difference in the risk of major adverse cardiovascular events (hazard ratio [HR]=0.94, 95% confidence interval [CI]: 0.65–1.35; P=0.73), stroke (HR=0.89, 95% CI: 0.62–1.27; P=0.52), myocardial infarction (HR=0.98, 95% CI: 0.70–1.37; P=0.91), all-cause mortality (HR=1.09, 95% CI: 0.73–1.65; P=0.67), and arrhythmia (risk ratio=0.64, 95% CI: 0.15–2.76; P=0.55) between degarelix and GnRH agonists. However, degarelix reduced the risk of heart failure (HR=0.56, 95% CI: 0.36–0.88; P=0.01).ConclusionFurther clarification on the effects of different androgen deprivation therapy modalities on cardiovascular disease is needed from future and larger prospective randomized controlled trials.